Math, asked by vinu2060, 4 months ago

3x^2 + 4x – 10: factorise it​

Answers

Answered by snehamayeebiswal10
1

Answer:

Simplifying

3x2 + 4x + -10 = 0

Reorder the terms:

-10 + 4x + 3x2 = 0

Solving

-10 + 4x + 3x2 = 0

Solving for variable 'x'.

Begin completing the square. Divide all terms by

3 the coefficient of the squared term:

Divide each side by '3'.

-3.333333333 + 1.333333333x + x2 = 0

Move the constant term to the right:

Add '3.333333333' to each side of the equation.

-3.333333333 + 1.333333333x + 3.333333333 + x2 = 0 + 3.333333333

Reorder the terms:

-3.333333333 + 3.333333333 + 1.333333333x + x2 = 0 + 3.333333333

Combine like terms: -3.333333333 + 3.333333333 = 0.000000000

0.000000000 + 1.333333333x + x2 = 0 + 3.333333333

1.333333333x + x2 = 0 + 3.333333333

Combine like terms: 0 + 3.333333333 = 3.333333333

1.333333333x + x2 = 3.333333333

The x term is 1.333333333x. Take half its coefficient (0.6666666665).

Square it (0.4444444442) and add it to both sides.

Add '0.4444444442' to each side of the equation.

1.333333333x + 0.4444444442 + x2 = 3.333333333 + 0.4444444442

Reorder the terms:

0.4444444442 + 1.333333333x + x2 = 3.333333333 + 0.4444444442

Combine like terms: 3.333333333 + 0.4444444442 = 3.7777777772

0.4444444442 + 1.333333333x + x2 = 3.7777777772

Factor a perfect square on the left side:

(x + 0.6666666665)(x + 0.6666666665) = 3.7777777772

Calculate the square root of the right side: 1.943650631

Break this problem into two subproblems by setting

(x + 0.6666666665) equal to 1.943650631 and -1.943650631.

Subproblem 1

x + 0.6666666665 = 1.943650631

Simplifying

x + 0.6666666665 = 1.943650631

Reorder the terms:

0.6666666665 + x = 1.943650631

Solving

0.6666666665 + x = 1.943650631

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-0.6666666665' to each side of the equation.

0.6666666665 + -0.6666666665 + x = 1.943650631 + -0.6666666665

Combine like terms: 0.6666666665 + -0.6666666665 = 0.0000000000

0.0000000000 + x = 1.943650631 + -0.6666666665

x = 1.943650631 + -0.6666666665

Combine like terms: 1.943650631 + -0.6666666665 = 1.2769839645

x = 1.2769839645

Simplifying

x = 1.2769839645

Subproblem 2

x + 0.6666666665 = -1.943650631

Simplifying

x + 0.6666666665 = -1.943650631

Reorder the terms:

0.6666666665 + x = -1.943650631

Solving

0.6666666665 + x = -1.943650631

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-0.6666666665' to each side of the equation.

0.6666666665 + -0.6666666665 + x = -1.943650631 + -0.6666666665

Combine like terms: 0.6666666665 + -0.6666666665 = 0.0000000000

0.0000000000 + x = -1.943650631 + -0.6666666665

x = -1.943650631 + -0.6666666665

Combine like terms: -1.943650631 + -0.6666666665 = -2.6103172975

x = -2.6103172975

Simplifying

x = -2.6103172975

Solution

The solution to the problem is based on the solutions

from the subproblems.

x = {1.2769839645, -2.6103172975}

Answered by PrashangLodwal
1

Step-by-step explanation:

HI this question is wrong it cannot be split .but of you want answer you will solve it by standard form

ax²+bx+c

in this equation a=3

b= 4

c= -10

Similar questions